Problematika Pembelajaran Online Bagi Anak Berkebutuhan Khusus Tunarungu di SLB Negeri Keleyan Pada Masa Pandemi Covid-19 - Syarifa Aini; Nova Estu Harsiwi (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to describe a problem that arises during distance learning for deaf children and teachers at the Keleyan State Special School. This type of research is descriptive qualitative. Data collection techniques use interviews and documentation. The subject of this research is a class teacher for children with special needs. The results of this research show that the problems that occur in online learning are that there are some parents who don't understand or even don't want to know about their children's learning process which is carried out remotely, parents who don't have cellphones, inadequate internet signals, and communication or delivery. The material carried out by the teacher with students does not run smoothly, which is different from learning carried out directly in the classroom so that the teacher touches it directly if the students do not understand.